Evaluating the Cost-Effectiveness of Lifestyle Modification versus Metformin Therapy for the Prevention of Diabetes in Singapore - Png, May Ee; Yoong, Joanne Su-Yin (PLOS ONE, 2014)
Background In Singapore, as diabetes is an increasingly important public health issue, the cost-effectiveness of pursuing lifestyle modification programs and/or alternative prevention strategies is of critical importance for policymakers. While the US Diabetes Prevention Program (DPP) compared weight loss through lifestyle modification with oral treatment of diabetes drug metformin to prevent/delay the onset of type 2 diabetes in pre-diabetic subjects, no data on either the actual or potential cost effectiveness of such a program is available for East or South-east Asian populations. This study estimates the 3-year cost-effectiveness of lifestyle modification and metformin among pre-diabetic subjects from a Singapore health system and societal perspective. Methodology Cost effectiveness was analysed from 2010–2012 using a decision-based model to estimate the rates of getting diabetes, healthcare costs and health-related quality of life. Cost per quality-adjusted life year (QALY) was estimated using costs relevant to the time horizon of the study from Singapore. All costs are expressed in 2012 US dollars. Principal Findings The total economic cost for non-diabetic subjects from the societal perspective was US25,867, US28,108 and US26,177 for placebo, lifestyle modification and metformin intervention respectively. For diabetic patients, the total economic cost from the societal perspective was US32,921, US35,163 and US33,232 for placebo, lifestyle modification and metformin intervention respectively. Lifestyle modification relative to placebo is likely to be associated with an incremental cost per QALY gained at US36,663 while that of metformin intervention is likely to be US6,367 from a societal perspective. Conclusion Based on adaptation of the DPP data to local conditions, both lifestyle modification and metformin intervention are likely to be cost-effective and worth implementing in Singapore to prevent or delay the onset of type 2 diabetes. However, the cost of lifestyle modification from the societal perspective would have to be reduced in order to match the cost-effectiveness of metformin intervention.